(untitled) (Contemporary Mathematics, 2021)
In this paper, it is considered the existence of solutions for a quasilinear system involving the p-Laplacian operator and gradient terms. The approach is based on sub-supersolution arguments and the Schauder’s Fixed Point Theorem. The results in this paper allow to consider several growth conditions in the gradient and complete some recent contributions.